Data and information sharing model in enhancing research collaboration among researchers: a preliminary study - Jusoh, Yusmadi Yah; Abdullah, Rusli; Sidi, Fatimah; Ishak, Iskandar; Tugiran, Yusnita; Marhaban, Mohammad Hamiruce; Napis, Suhaimi (IEEE, 2019)
There are variuos form of data and information that has been produced and used by the researchers in order to perform their research work. However, there is a lack of mechanism on how data and information can be managed in storing, accesing, reusing and sharing the OR. Hopefully the OR can be utilised by other researchers community (RC) in order to save cost, time, and effort in getting or using this OR. Therefore, there is a need of OR model especially in the university to enhance or encourage the RC to work collaboratively in sharing this data and information among them. By using this OR sharing model, the university can be promoted of data and information of open OR that has been acquired and used by the researcher not just for the purpose of individually only but also can be used by other researchers as a team collaboratively.